A ratiometric electrochemical aptasensor for ochratoxin A detection. Issue 7 (8th February 2021) - Liang, Xiujun; Zhao, Fengjuan; Xiao, Chengui; Yue, Shuang; Huang, Yawei; Wei, Min
Abstract: With the superiority of providing a more accurate signal through their self‐referencing capability and reducing the environmental influence, a ratiometric electrochemical aptasensor was proposed for ochratoxin A (OTA) detection using methylene blue (MB) and ferrocene (Fc) as signal probes. The magnetic beads were used for the immobilization of OTA aptamer (Apt). When OTA and MB‐labeled complementary DNA (cDNA‐MB) were added, OTA combined with Apt, whereas cDNA‐MB released and existed in the supernatant after magnetic separation. By dropping the supernatant onto the electrode modified with HP‐Fc, the hairpin structure of HP‐Fc was opened by the hybridization between cDNA‐MB and HP‐Fc. As a result, MB was close to the electrode surface, whereas Fc was away from the electrode surface. Based on the value of IMB /IFc, OTA was detected sensitively and specifically. Under the optimal conditions, a linear relationship in the range of 0.005–50 ng/ml was obtained with the detection limit of 2.35 pg/ml. The aptasensor showed high anti‐interference toward AFB1, FB1, ZEN, and OTB. The aptasensor was applied to detect OTA in spiked corn samples, and the recoveries were 93–102%. This method provides a great potential for the development of sensitive biosensing platform for food safety. Abstract : A simple and sensitive electrochemical ratiometric aptasensor was developed for ochratoxin A (OTA) detection based on hairpin DNA, homogeneous reaction system, and magnetic separation. In the presence of OTA, methylene blue is close to the electrode surface, whereas ferrocene is away from the electrode surface. These changes cause the increase of IMB, accompanied by the decrease of that of the IFc, leading to "signal‐off" and "signal‐on" elements for electrochemical ratiometric readout.